2006
DOI: 10.1038/sj.ijo.0803361
|View full text |Cite
|
Sign up to set email alerts
|

Does physical activity equally predict gain in fat mass among obese and nonobese young adults?

Abstract: Background: Differences in energy metabolism and physical activity (PA) may contribute to the long-term regulation of body weight (BW). Objective: To examine the associations between metabolic determinants, energy expenditure and objectively measured components of PA with change in BW and fat mass (FM). Design: Prospective (4 years.), case-control study in obese (n ¼ 13) and normal weight (n ¼ 15) young adults. Measurements: At baseline, we measured resting metabolic rate, substrate oxidation, movement economy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 41 publications
1
18
1
2
Order By: Relevance
“…Ekelund et al 63 examined the relationship between changes in weight, fat mass and physical activity among obese and normal weight adolescents in Sweden. They found that both the normal weight and obese groups gained weight and fat mass over the 4-year follow-up period.…”
Section: Energy Imbalance and Childhood Obesity Sn Bleich Et Almentioning
confidence: 99%
“…Ekelund et al 63 examined the relationship between changes in weight, fat mass and physical activity among obese and normal weight adolescents in Sweden. They found that both the normal weight and obese groups gained weight and fat mass over the 4-year follow-up period.…”
Section: Energy Imbalance and Childhood Obesity Sn Bleich Et Almentioning
confidence: 99%
“…asimismo, en un estudio transversal en preadolescentes, los índices de adiposidad estuvieron inversamente relacionados con las horas de actividad física moderada y vigorosa 13 . Sin embargo, en un estudio de seguimiento en adultos jóvenes, se observó que a pesar que la intensidad de la actividad física no varió en el tiempo (4 años), sí lo hizo la grasa corporal, sugiriendo que esta ganancia se debería a un aumento de la ingesta, la que no fue cuantificada 12 . Nuestro estudio coincide con un reporte previo en el que se señala que los niños y adolescentes que consultan por obesidad tienen una ingesta adecuada, pero una actividad física muy deficiente 15 .…”
Section: Resultsunclassified
“…Hay controversias en relación a cual sería el factor predominante en la génesis del sobrepeso en la población pediátrica, probablemente por la diversidad de diseños utilizados y por las diferencias socioculturales entre las muestras [12][13][14] . a nivel nacional, en escolares de centros educacionales de la Región Metropolitana, una evaluación cualitativa reveló que la calidad de los hábitos de ingesta era mejor que los de actividad física 11 .…”
unclassified
“…NIH-PA Author Manuscript NIH-PA Author Manuscript moderate and vigorous physical activity (MPA and VPA) children routinely perform and how these levels relate to obesity (Ekelund et al, 2007;Pate et al, 2002).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%